At the Speed of Light - G Venkataraman (Hyderabad, 2016)
This book is about the Theory of Relativity. The story of Relativity is, in a sense, the story of one man$1 (BAlbert Einstein. The book deals only with the Special Theory, which you will find is not very difficult to understand.s
English
Keywords: Physics